Simulacija strežnih sistemov z GPSS - Guid, Nikola (Informatica (Ljubljana), 1979)
This paper deals resolution of the most different fundamental types of queueing systems by the simulation with GPSS. The problems in validating simulation results and recommendations in improvement of simulation precision are considered.
Keywords: GPSS; simulacije; strežni sistemi